A Reexamination of Traditional Hypotheses about the Term Structure: A Comment - MCCULLOCH, J. HUSTON (Journal of Finance, 1993)
ABSTRACT An example of a continuous time economy is given whose general equilibrium term structure of interest rates obeys the Expectations Hypothesis for continuously compounded interest rates and returns, contradicting the 1981 claim by Cox, Ingersoll, and Ross that such an economy is mathematically impossible. This example does not generate exploitable arbitrage opportunities of the type Cox, Ingersoll, and Ross claim must arise. The “Logarithmic Expectations Hypothesis,” as we call it, it therefore an acceptable benchmark from which to measure term premia in continuous time term structure modeling.